Makanan dan Kebiasaan Makan Siput Gonggong (Laevistrombus turturella) di Perairan Pulau Penyengat Kota Tanjungpinang - Nur Afni Nezaputri; Dedy Kurniawan; Ani Suryanti; Muzahar; Susiana (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Food and Feeding Habits of Dog Conch (Laevistrombus turturella) on Penyengat Island, Tanjungpinang. Dog conch (Laevistrombus turturella) in Tanjungpinang, including commodities of high economic value. The purpose of this study was determine the ratio of the length of gut and the total body length, type of food and feeding habits of dog conch on the Penyengat Island, Tanjungpinang, Riau Islands. The study was conducted from May to November 2019. The sampling location was determined based on the purposive sampling method. The station were divided into 3 stations based on 1) the catch zone of the dog conch, 2) the characteristics of the dog conch habitat and 3) activities along the coast. Analysis of the data were provided the ratio of the length of gut and the total body length, index of preponderance, Viscero Somatic Index (VSI), total organic matter and index of electivity. The results showed that the ratio of the length of gut and the total body length of the dog conch were 1,53; 1,60; 1,66 and classified as an omnivore based on the ratio of the length of gut and the total body length. Types of dog conch food that have been found were detritus and microalgae class Bacillariophyceae, Chlorophyceae, and Crustaceans. The feeding habits of dog conch were detritus with the index of preponderance of 65-70% as the main food. VSI values were ranged from 24,27 to 36,35%. Value Index of electivity were ranged from 0,99-1% or close to 1.